High synovial expression of the inhibitory FcγRIIb in rheumatoid arthritis - Magnusson, Sofia E (BioMed Central, 2007)
Activating Fc gamma receptors (FcγRs) have been identified as having important roles in the inflammatory joint reaction in rheumatoid arthritis (RA) and murine models of arthritis. However, the role of the inhibitory FcγRIIb in the regulation of the synovial inflammation in RA is less known. Here we have investigated synovial tissue from RA patients using a novel monoclonal antibody (GB3) specific for the FcγRIIb isoform. FcγRIIb was abundantly expressed in synovia of RA patients, in sharp contrast to the absence or weak staining of FcγRIIb in synovial biopsies from healthy volunteers. In addition, the expression of FcγRI, FcγRII and FcγRIII was analyzed in synovia obtained from early and late stages of RA. Compared with healthy synovia, which expressed FcγRII, FcγRIII but not FcγRI, all activating FcγRs were expressed and significantly up-regulated in RA, regardless of disease duration. Macrophages were one of the major cell types in the RA synovium expressing FcγRIIb and the activating FcγRs. Anti-inflammatory treatment with glucocorticoids reduced FcγR expression in arthritic joints, particularly that of FcγRI. This study demonstrates for the first time that RA patients do not fail to up-regulate FcγRIIb upon synovial inflammation, but suggests that the balance between expression of the inhibitory FcγRIIb and activating FcγRs may be in favour of the latter throughout the disease course. Anti-inflammatory drugs that target activating FcγRs may represent valuable therapeutics in this disease.